SIVI KRİSTALLERİN ELEKTRO-OPTİK VE FAZ GEÇİŞİ ÖZELLİKLERİ - COŞKUN, BURHAN (Fırat Üniveristesi, 2007)
Bu çalışmada, farklı polimerler katkılandırılmış 4-siyano-4'-n-pentilbifenil sıvı kristalinin elektro-optik ve faz geçişi özellikleri araştırıldı. Sıvı kristallerin dielektrik anizotropi ve dielektrik relaksasyon özellikleri dielektrik sepktroskopi metodu ile analiz edildi. Dielektrik anizotropi özellikleri polimer katkılamasıyla değişti. Sıvı kristallerin dielektrik relaksasyon mekanizması Debye tipi relaksasyon mekanismasıdır. Faz geçiş sıcaklıkları dielektrik-sıcaklık metodu ile belirlendi. Sıvı kristallerin elektro-optik ve faz geçişi özelliklerinin polimer katkılamasıyla değiştiği gözlendi. Anahtar Kelimeler: Sıvı kristal, dielektrik anizotropi, polimer, faz geçişi

In this study, the electro-optical and phase transition properties of 4-cyano-4?-npentylbiphenyl liquid crystal doped by various polymers have been investigated. The dielectrical anizotropy and dielectrical relxation properties of the liquid crystals have been analyzed by dielectrical spectroscopy method. The dielectrical anisotropy values were changed with doping of polymer. The dielectrical relaxation mechansim of the liquid crystals is Debye type relation mechanism. The phase transition temperatures were determined by dielectric-temperature method. It was observed that the electro-optical and phase transition properties of the liquid crystals were changed with doping of polymer. Keywords: Liquid crystal, dielectrical anisotropy, polymer, phase transition
The electro-optical and phase transition properties of liquid crystals
Keywords: Fizik ve Fizik Mühendisliği